Perlindungan Hukum terhadap Pekerja PKWTT yang Belum Mendapat Hak BPJS Ketenagakerjaan berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Aldi Prasetyo; Dipo Wahyoeno Hariyono (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
Currently, there are still many workers in Indonesia who have not registered as BPJS Ketenagakerjaan participants, especially workers with PKWTT (Specific Time Work Agreement) status. Several companies still have not enrolled their workers in BPJS Ketenagakerjaan. Hence, this research aims to find out how to find out the legal protection of workers against PKWTT workers who have not received BPJS Ketenagakerjaan rights based on Law Number 13 of 2003 on Manpower. The method used in the preparation of this research is a normative juridical research method, namely legal research that is only aimed at written regulations and other legal materials. This study aims to determine the legal protection for PKWTT workers who have not received their rights of Labor Social Security Administration Agency based on Law Number 13 of 2003 on Manpower.